AN ULTRA-CAPACITOR INTEGRATED DYNAMIC VOLTAGE RESTORER FOR POWER QUALITY ENHANCEMENT IN A THREE-PHASE DISTRIBUTION SYSTEM USING AN ADAPTIVE NEURO-FUZZY INTERFERENCE SYSTEM CONTROLLER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
Power quality voltage-related issues sag and swell are recognized as recurrent, severe threats in the distribution systems that lead to an enormous loss in productivity and profitability for both utilities and customers. Dynamic voltage restorer (DVR) is a well-known commercial solution for the issues of sag and swell. There has been an enhanced interest in incorporating Renewable energy resources into the dc input source of custom power devices. The chosen energy storage device should be capable of affording peak power with less duration. Ultracapacitors (UCAPs) are the better choice for energy storage with less cost and are also suited for mitigating sag and swell issues, which need enormous power with minimum duration. The novelty of this paper is its contribution to the design of an integrated renewable UCAP energy storage device as a dc source for DVR (UCAP-DVR). An improved synchronous reference frame (SRF) algorithm with an adaptive neuro-fuzzy interference system (ANFIS) controller is employed to enhance the compensation capability of the UCAP-DVR system against unbalanced sag and swell problems. It also provides active power support to the grid. This integration proposes a suitable bidirectional converter to afford a stiff DC input voltage for DVR.Many complications in designing and controlling the voltage source inverter (VSI) and the proposed converter are discussed. The proper integration of UCAP-DVR with the distribution grid using the SRF-ANFIS Controller was done in MATLAB simulation. The behavior of the proposed DVR for the problems of both balanced and unbalanced voltage sag and swell was discussed. A comparison has been made with the SRF-PI controller to outline the importance of the proposed controller for UCAP-DVR. Hardware experimental setup of this integrated UCAP-DVR system is developed, and the ability to provide voltage sag and swell compensation in all three phases to the distribution grid is dynamically tested successfully.
Keywords: Power Quality (PQ); Dynamic Voltage Restorer (DVR); Voltage sag; Voltage swell; Adaptive neuro-fuzzy (ANFIS) controller; Ultracapacitor; Synchronous reference frame theory